2014
DOI: 10.1590/s0100-06832014000400007
|View full text |Cite
|
Sign up to set email alerts
|

Fungos micorrízicos arbusculares em fitofisionomias do Pantanal da Nhecolândia, Mato Grosso do Sul

Abstract: O bioma Pantanal é reconhecido como uma das maiores extensões úmidas contínua do planeta, com fauna e flora de rara beleza e abundância. Estudos para acessar a diversidade de fungos micorrízicos arbusculares (FMA) nesse ambiente são inexistentes. O objetivo deste trabalho foi avaliar a ocorrência de FMA nas diferentes fitofisionomias do Pantanal da Nhecolândia, Mato Grosso do Sul. Foram coletadas amostras de solo no período seco e chuvoso em um Neossolo Quartzarênico, em fitofisionomias sujeitas a distintos re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
3
1
2
Order By: Relevance
“…In protected and sustainably managed areas of Atlantic Forest, the management, plant community and soil iron and fine sand was found as factors influencing AM fungal communities (Pereira et al 2018). Nevertheless, as in our study, relationships between AMF community structure and plant community have also been shown in land-use types and biomes other than those of the Atlantic Forest (Davison et al 2011;Gomide et al 2014;Johnson et al 1992;Mueller et al 2014). Thus, our study expands on this research by showing that variations in AMF indices and species are best explained by phytophysiognomy, followed by soil texture and then soil chemical characteristics.…”
Section: Final Considerationscontrasting
confidence: 38%
See 1 more Smart Citation
“…In protected and sustainably managed areas of Atlantic Forest, the management, plant community and soil iron and fine sand was found as factors influencing AM fungal communities (Pereira et al 2018). Nevertheless, as in our study, relationships between AMF community structure and plant community have also been shown in land-use types and biomes other than those of the Atlantic Forest (Davison et al 2011;Gomide et al 2014;Johnson et al 1992;Mueller et al 2014). Thus, our study expands on this research by showing that variations in AMF indices and species are best explained by phytophysiognomy, followed by soil texture and then soil chemical characteristics.…”
Section: Final Considerationscontrasting
confidence: 38%
“…Some authors have reported that vegetation type and soil texture have a greater influence on AMF community than soil chemical properties (Lovelock et al 2003;Mathimaran et al 2005;Silva et al 2015a;Sousa et al 2018). However, other studies have found that while soil chemistry and vegetation type do modify AMF communities, soil texture does not (Pagano et al 2013;Gomide et al 2014). Yet another study has shown that management, plant community, soil iron and fine sand influence AM fungal communities in protected and sustainably managed areas of the Atlantic Forest (Pereira et al 2018).…”
Section: Contribution Of Individual Soil Properties On Determining Ammentioning
confidence: 99%
“…Trufem et al (1989) reported 0.5 spores/g in the soil of the Atlantic Forest of Cardoso Island (Ilha do Cardoso, Brazil), while Souza et al (2003) reported 0.34-8.6 spores/g of the soil in a seasonally dry forest called Caatinga in northeast Brazil. Lima et al (2013) found 0.65-4.07 spores/g in eucalyptus plantations, and Gomide et al (2014) reported 0.26-9.32 spores/g in a semideciduous forest. The density of spores in the present study was also greater than the density obtained by Carvalho et al (2012) (0.18-0.4 spores/g) in the same region.…”
Section: Discussionmentioning
confidence: 98%
“…Fernandes (2009) comenta ainda, que as práticas de manejo e uso do solo também podem alterar a composição quantitativa e qualitativa desses fungos no solo. Gomide (2013) relatou que os aspectos ecológicos de vegetação podem explicar melhor a diversidade de FMAs do que os atributos químicos do solo, pois é uma tentativa de demonstrar os efeitos de processos locais atuando sobre a diversidade destes fungos no solo. Nesse sentido, a rotação de culturas e a maior diversidade de espécies de plantas em um ecossistema poderá promover aumento na população dos FMAs nativos do solo, beneficiando as plantas de interesse agrícola e florestal e os cultivos subsequentes.…”
Section: Introductionunclassified